A rare case of sirenomelia (Indian Journal of Case Reports, 2024)
Sirenomelia also called mermaid syndrome is a congenital, rare, lethal, multisystemic human malformation of unknown etiology. The characteristic feature of sirenomelia is the fusion of the lower limbs, resulting in the appearance of a mermaid’s tail, and thus the name “mermaid syndrome.” This condition is also characterized by various severe urogenital abnormalities and the presence of a singular umbilical cord blood vessel, and it is more common in infants of diabetic mothers and in monozygotic twins. The incidence is around 1 in 60,000–70,000 pregnancies. The majority of affected fetuses are stillborn, whereas the rest of the live-born die in the early neonatal period due to complications of the gastrointestinal and urogenital systems. We are reporting a case of sirenomelia in a neonate born to an unregistered multipara mother. The baby had perinatal asphyxia, sirenomelia, dextrocardia, low set ears, lymphatic malformation, bilateral renal agenesis, absent external genitalia and anus, single umbilical artery, and congenital corneal clouding. There was no antenatal ultrasonography done and the baby died at 6 h of life.